Associative Thinking: Different Languages = Different Types of Thinking? - Zavjalova, Marija (Respectus Philologicus, 2001)
The results of the associative experiment with Russian-Lithuanian bilinguals show that the form and content of the associative word relations depend on the language: probably the verbal experience is held in the mind connected with the language, in which it was received. So in the thought of the bilingual two complexes of the images of the world, attached to the two languages, are formed. That’s why the bilinguals’ speech and thought might differ from the monolinguals’ ones. In the speech practice on the second language the stereotypes, borrowed from it, play an important role. The semantic field of a word is composed of the stereotype relations complex. Because of that the acquisition of the stereotype phrases of the second language is the necessary condition for successful speech in that language. The more "stereotype" thought of bilinguals does not damage the development of the speech and thought. On the contrary: the bilingual has in his mind more complicated system of the world images than the monolingual and he receives more wide information about the world, because of that he can look at it in different ways choosing one or another language (and mental) system.